Nutritive Value of Distillers Dried Grains with Soluble and Broiler Performance at Starter Period - Shalash, S.M.M.; El-Wafa, S. Abou; Sayed, M.A.M.; El-Gabry, Hoda E.; Ramadan, Nehad A.; Mohamed, Manal S. (International Journal of Poultry Science, 2009)
Three experiments were conducted to evaluate nutritive value of Distillers Dried Grains with Solubles (DDGS) in starter broiler diets using different levels (0, 6, 9 or 12%). Exp. I was design to determine the digestibility coefficients of nutrients for DDGS using 16 cockerels, 40 weeks old compared to a mixture of yellow corn and DDGS 1:1 or 100% DDGS. Feeding cockerels 100% DDGS reduced Crude Protein (CP) from 93.60-92.17%, Ether Extract (EE) from 82.37-75.52%, Crude Fiber (CF) from 27.30-23.47, NFE from 82.85-55.45%) and Organic Matter (OM) from 83.30-69.30%) compared to those fed 50% DDGS. Exp. II was designed to evaluate the nutritive value of DDGS protein using Total Protein Efficiency (TPE) technique. A total number of 80 unsexed one-day old Arbor Acers broiler chicks were distributed between 2 treatments of 40 chicks each in four replicates (10 chicks each) and fed commercial diet (22% CP and 3000 Kcal ME/Kg) for two weeks. On the 14th day, the chicks were fed experimental diets (18% CP) in which cereals (yellow corn and fine wheat bran) provided 6% of dietary CP, while the test material (DDGS) provided 12%, from 14 up to 28 days of age. Significant reduction took place in body weight gain, feed intake, protein intake and T.P.E. value for chicks fed diets containing DDGS compared with those fed diets containing soybean meal as a source of protein. Exp. III, was design to evaluate DDGS at different levels: 0, 6, 9 or 12% in starter broiler diets. A total number of 240 unsexed one-week old Arbor Acers broiler chicks were distributed into 4 treatments of 60 chicks each in six replicates (10 chicks each). Diets were formulated to contain 22% CP and 3070 Kcal ME/Kg at starter period (1-4wks of age). Performance and Relative Economic Efficiency (REE) of chicks fed diets with 6% DDGS approximately equaled those fed control diet (corn/soy). However, reduction in body weight and body weight gain. Took place in both 9 and 12% DDGS supplemental diets, being significant in the 12% diet. A noticeable reduction in REE values took place between treatments. The 6% DDGS level equal almost the control performance. The 9 and 12% DDGS treatments showed lower REE than both control and the 6% level. Inclusion of DDGS in the broiler diets had no effect on mortality rate.